Electro-optic tuning of split ring resonators embedded in a liquid crystal - Atorf, Bernhard; Mühlenbernd, Holger; Muldarisnur, Mulda; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (Optics Letters)

Measurement of group velocity dispersion in a solid-core photonic crystal fiber filled with a nematic liquid crystal - Wahle, Markus; Kitzerow, Heinz-Siegfried (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

Bright squeezed-vacuum source with 11 spatial mode - Pérez, A. M.; Iskhakov, T. Sh.; Sharapova, Polina; Lemieux, S.; Tikhonova, O. V.; Chekhova, M. V.; Leuchs, G. (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

Nonlinear dynamics of Airy-vortex 3D wave packets: emission of vortex light waves - Driben, Rodislav; Meier, Torsten (Optics Letters)
The dynamics of 3D Airy-vortex wave packets is studied under the action of strong self-focusing Kerr nonlinearity. Emissions of nonlinear 3D waves out of the main wave packets with the topological charges were demonstrated. Because of the conservation of the total angular momentum, charges of the emitted waves are equal to those carried by the parental light structure. The rapid collapse imposes a severe limitation on the propagation of multidimensional waves in Kerr media. However, the structure of the Airy beam carrier allows the coupling of light from the leading, most intense peak into neighboring peaks and consequently strongly postpones the collapse. The dependence of the critical input amplitude for the appearance of a fast collapse on the beam width is studied for wave packets with zero and nonzero topological charges. Wave packets carrying angular momentum are found to be much more resistant to the rapid collapse.

Coupled Airy breathers - Driben, R.; Konotop, V. V.; Meier, Torsten (Optics Letters)
The dynamics of two component-coupled vectorial Airy beams is investigated. In the linear propagation regime, a complete analytic solution describes the breather-like propagation of two components that feature nondiffracting self-accelerating Airy behavior. The superposition of two beams with different input properties opens the possibility of designing more complex nondiffracting propagation scenarios. In the strongly nonlinear regime, the dynamics remain qualitatively robust as is revealed by direct numerical simulations. Because of the Kerr effect, the two beams emit solitonic breathers whose coupling period is compatible with the remaining Airy-like beams. The results of this study are relevant for the description of photonic and plasmonic beams that propagate in coupled planar waveguides, as well as for birefrigent or multiwavelength beams.

Time-to-space conversion of ultrafast waveforms at 155 μm in a planar periodically poled lithium niobate waveguide - Shayovitz, Dror; Herrmann, Harald; Sohler, Wolfgang; Ricken, Raimund; Silberhorn, Christine; Marom, Dan M. (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

Testing spectral filters as Gaussian quantum optical channels - Laiho, K.; Christ, A.; Cassemiro, K. N.; Silberhorn, Christine (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

High-visibility, high-order lensless ghost imaging with thermal light - Chen, Xi-Hao; Agafonov, Ivan N.; Luo, Kai Hong; Liu, Qian; Xian, Rui; Chekhova, Maria V.; Wu, Ling-An (Optics Letters)

Lensless ghost imaging with true thermal light - Chen, Xi-Hao; Liu, Qian; Luo, Kai Hong; Wu, Ling-An (Optics Letters)

Shaping the spatiotemporal dynamics of the electron density in a hybrid metal-semiconductor nanostructure - Reichelt, Matthias; Meier, Torsten (Optics Letters)
A one-dimensional semiconductor nanostructure is locally excited through a metal aperture. It is shown that the electron density can be coherently localized at desired spatial and temporal positions by using nontrivially shaped laser pulses. To obtain the optimized laser field, Bloch equations for a tight-binding model system are solved together with a genetic pulse-shaping algorithm. Full three-dimensional finite-difference time-domain (FDTD) simulations of the Maxwell–Bloch equations confirm the predicted coherent spatiotemporal control.